Point-of-care laboratory of pathogen diagnosis in rural Senegal. - Cheikh Sokhna; Oleg Mediannikov; Florence Fenollar; Hubert Bassene; Georges Diatta; Adama Tall; Jean-François Trape; Michel Drancourt; Didier Raoult (Public Library of Science (PLoS), 2013)
BACKGROUND: In tropical Africa, where the spectrum of the bacterial pathogens that cause fevers is poorly understood and molecular-based diagnostic laboratories are rare, the time lag between test results and patient care is a critical point for treatment of disease. METHODOLOGY/PRINCIPAL FINDINGS: We implemented POC laboratory in rural Senegal to resolve the time lag between test results and patient care. During the first year of the study (February 2011 to January 2012), 440 blood specimens from febrile patients were collected in Dielmo and Ndiop villages. All samples were screened for malaria, dengue fever, Borrelia spp., Coxiella burnetii, Tropheryma whipplei, Rickettsia conorii, R. africae, R. felis, and Bartonella spp. CONCLUSIONS/SIGNIFICANCE: We identified DNA from at least one pathogenic bacterium in 80/440 (18.2%) of the samples from febrile patients. B. crocidurae was identified in 35 cases (9.5%), and R. felis DNA was found in 30 cases (6.8%). The DNA of Bartonella spp. was identified in 23/440 cases (4.3%), and DNA of C. burnetii was identified in 2 cases (0.5%). T. whipplei (0.2%) was diagnosed in one patient. No DNA of R. africae or R. conorii was identified. Among the 7 patients co-infected by two different bacteria, we found R. felis and B. crocidurae in 4 cases, B. crocidurae and Bartonella spp. in 2 cases, and B. crocidurae and C. burnetii in 1 case. Malaria was diagnosed in 54 cases. In total, at least one pathogen (bacterium or protozoa) was identified in 127/440 (28.9%) of studied samples. Here, the authors report the proof of concept of POC in rural tropical Africa. Discovering that 18.2% of acute infections can be successfully treated with doxycycline should change the treatment strategy for acute fevers in West Africa.